Autonomic Function in Peripheral Nerve Regeneration Especially in Radial and Ulnar Nerve Injuries after Microsurgery: A Systematic Review - Ria Margiana (Journal of Global Pharma Technology, 2016)
This literature review seeks to understand the difference in autonomic function of radial and ulnar nerve injuries after microsurgery. During this surgery, additional damage to nerves is also experienced. This research focused on peer-reviewed articles from Pubmed-NCBI database. This is a medical database which features medical peer-reviewed articles on various illnesses treatments and outcomes. The eligibility criteria used were that the article must be full text, published within the past 10 years, written in English language, and featured the keywords-radial nerve injury, ulnar nerve injury and microsurgery. There was no specific characteristic for participants as all individuals with injury were considered. The search from the database yielded 121 initial articles. Of this number, 33 were excluded for being editor comments and no full texts. This had led to 88 remaining articles which were further screened to remove articles written in other languages and those which were older than 10 years. This featured a total of 43 articles. Of this remaining total, only 30 articles were used. The other 15 were excluded as a result of research reliability issues. The procedures used in the articles featured a lot of limitations which questioned the validity of their results. This paper concludes with a summary of the analysis of the difference in autonomic function of the radius and ulna after microsurgery.Keywords: Autonomic function, Radial nerve, Ulnar nerve, Microsurgery.